Manajemen Pengembangan Karakter Siswa dalam Konteks Pendidikan Islam - Nuruddin, Nuruddin; Fauzi, M Asif Nur (Lembaga Yasin AlSys, 2025)
The limited research on comprehensive character development management models in Islamic educational institutions at the district level forms the background of this study, particularly in the context of a moral crisis among youth that poses significant implications for the nation's future and the relevance of Islamic education. This study aims to analyze and describe the management of student character development encompassing the aspects of planning, organizing, implementation, and evaluation at Madrasah Aliyah. A qualitative method with a multi-case study approach was employed involving three purposively selected madrasahs. Data were collected through in-depth interviews with school leaders, teachers, and students, observation of school activities, and document analysis, including curricula and school regulations. Data analysis followed the model of Miles, Huberman, and Saldana. The findings reveal that the madrasahs apply an integrated character development model combining modern management principles (POAC: Planning, Organizing, Actuating, Controlling) with Islamic values, where exemplary conduct (uswah hasanah) serves as the foundational approach. Planning is reflected in the vision, mission, and curriculum documents; organizing involves role delegation among teachers and collaboration with parents; implementation is carried out through habituation of Islamic values, moral guidance, and enforcement of discipline; while evaluation is conducted through both formal and informal means. This study contributes to the theory of leadership and Islamic character education and recommends strengthening the managerial and spiritual capacities of teachers to enhance the effectiveness of character development. Further research is suggested to evaluate the long-term impact of this model on madrasah alumni outcomes.